Analisis Kinerja Biaya dan Waktu dengan Metode Earned Value Analysis (Studi Kasus: Revitalisasi Pasar Gembrong Sukasari) - Saputro, Teguh Eko; Mahendra, Muhammad Oka; Putra, Al Fiillian Sah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The construction industry in Indonesia continues to grow, yet projects often face deviations from initial plans, particularly concerning cost overruns and schedule delays. This study evaluates the cost and schedule performance of the Revitalization of Pasar Gembrong Sukasari Market using Earned Value Analysis (EVA), a quantitative method for monitoring project efficiency. Data were derived from weekly progress reports, S-curve projections, and the project’s budget plan (RAB). At week 35, the Planned Value (BCWS) was IDR 55,052,769,527.00, while the Earned Value (BCWP) and Actual Cost (ACWP) both amounted to IDR 49,830,463,809.67. The Cost Variance (CV) of IDR 0 and Cost Performance Index (CPI) of 1.00 indicated precise adherence to the budget. However, a Schedule Variance (SV) of -IDR 5,222,305,717.33 and a Schedule Performance Index (SPI) of 0.905 revealed significant schedule delays. These findings demonstrate that while the project maintained financial efficiency, critical time management inefficiencies led to schedule overruns. The study underscores the effectiveness of EVA in identifying performance gaps and highlights the need for improved scheduling strategies to align time and cost objectives in construction management.